Understanding the biology Of CD24 - Sajid, Saira (2018)
Cancers are amongst the leading cause of morbidity and mortality today. Besides the tremendous amount of research, it still appears to be a long way till we can fully understand the pathology and find its cure. Scientists are still striving to find out the precise pathogenesis, factors leading to progression and the mechanisms of spread of cancers. The ultimate objective is to find out how these can be prevented and treated. Many molecules are a focus of attention in this regard and CD24 is amongst them. CD24 is normally present on haematopoietic cells and embryonal epithelial cells but the expression is generally lost with cellular maturity and differentiation.